2019
DOI: 10.1097/cm9.0000000000000329
|View full text |Cite
|
Sign up to set email alerts
|

Sleep fragmentation as an important clinical characteristic of sleep disorders in Parkinson's disease

Abstract: Background:Sleep disorders are one of the earliest non-motor symptoms of Parkinson's disease (PD). Sleep disorders could, therefore, have value for recognition and diagnosis in PD. However, no unified classification and diagnostic criteria exist to evaluate sleep disorders by polysomnography (PSG). Utilizing PSG to monitor sleep processes of patients with PD and analyze sleep disorder characteristics and their relationship with demographic parameters could aid in bridging this gap. This preliminary study aimed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 25 publications
1
12
0
Order By: Relevance
“…This has revealed that fragmentation appears to be an important component of HD sleep architectural disturbance, including in the premanifest phase. Once again this parallels findings in Alzheimer's and Parkinson's, where sleep fragmentation in particular has been identified as a feature of both premonitory and established disease [62][63][64][65][66].…”
Section: Sleep Architecture Abnormalitiessupporting
confidence: 71%
“…This has revealed that fragmentation appears to be an important component of HD sleep architectural disturbance, including in the premanifest phase. Once again this parallels findings in Alzheimer's and Parkinson's, where sleep fragmentation in particular has been identified as a feature of both premonitory and established disease [62][63][64][65][66].…”
Section: Sleep Architecture Abnormalitiessupporting
confidence: 71%
“…Numerous PSG‐based case–control studies examining sleep in PD have demonstrated distinct changes in each of the different sleep stages 16,17,19,20,22‐24,39‐61 …”
Section: Cortical Electrophysiological Changes In Pd During Sleep — Eegmentioning
confidence: 99%
“…34,36,38 Cortical Electrophysiological Changes in PD During Sleep -EEG Numerous PSG-based case-control studies examining sleep in PD have demonstrated distinct changes in each of the different sleep stages. 16,17,19,20,[22][23][24]…”
Section: Overview Of Normal Sleep Physiologymentioning
confidence: 99%
See 2 more Smart Citations